Upaya Pengurangan Tingkat Kecacatan Cabai Pasca Panen Pada Jalur Rantai Pasok - Wijaya, William Dwi; Sutapa, I Nyoman (Jurnal Titra, 2013)
The handling qualities of Â Malang Chili throughout its supply chain system is still considered low, as there are lots of faults took place during the process that led to the declining quality of the chilies. It is recommended to plan a handling procedure of post-harvested chilies in order to enhance a better quality. This study will try to design a quality plan to address those issues, using methods such as pareto diagram and cause-and-effect diagram. Observations result concluded that problems occurred are due to various factors, namely human error, method and environment. On farmers supply chain have the biggset disability obtained is wilting. Meanwhile, wholesalers supply chain have the biggest disability namely dented. Quality plan arranged use to guide early improvement in the conduct of each post-harvest process chili in Malang to overcome the factors that cause chili damaged such as drying, tranportation and selling.